Saladin the sultan who vanquished the crusaders and built an Islamic empire - Man, John 1941- (De Capo Press, a member of the Perseus Books Group, 2016)
Saladin remains one of the most iconic figures of his age. As the man who united the Arabs and saved Islam from Christian crusaders in the twelfth century, he is the Islamic world's preeminent hero. A ruthless defender of his faith and brilliant leader, he also possessed qualities that won admiration from his Christian foes. But Saladin is far more than a historical hero. Builder, literary patron, and theologian, he is a man for all times, and a symbol of hope for an Arab world once again divided. Centuries after his death, in cities from Damascus to Cairo and beyond, to the Arabian Peninsula and the Gulf, Saladin continues to be an immensely potent symbol of religious and military resistance to the West. He is central to Arab memories, sensibilities, and the ideal of a unified Islamic state. John Man charts Saladin's rise to power, his struggle to unify the warring factions of his faith, and his battles to retake Jerusalem and expel Christian influence from Arab lands. Saladin explores the life and enduring legacy of this champion of Islam while examining his significance for the world today.